Loop-Mediated Isothermal Amplification Coupled With Nanoparticle-Based Lateral Biosensor for Rapid, Sensitive, and Specific Detection of Bordetella pertussis - Sun, Chunrong; Xiao, Fei; Fu, Jin; Huang, Xiaolan; Jia, Nan; Xu, Zheng; Wang, Yi; Cui, Xiaodai (Frontiers in Bioengineering and Biotechnology, 2022)
Bordetella pertussis is the most frequent causative agent for pertussis, which is a highly contagious disease. Here, we developed a method based on loop-mediated isothermal amplification (LAMP) and nanoparticle-based lateral flow biosensor (LFB) for the timely diagnosis of B. pertussis infections. A set of six primers was designed for LAMP reactions, and the LAMP results were rapidly and visually indicated using LFB. The recommended condition for the B. pertussis LAMP reactions is 40 min at 66°C. Our results confirmed that the LAMP-LFB assay could specifically detect B. pertussis and did not cross-react with non-B. pertussis isolates. The sensitivity of the B. pertussis LAMP-LFB assay was 50 fg per reaction. In particular, 108 nasopharyngeal swab (NPS) samples were collected to evaluate the B. pertussis LAMP-LFB assay, and the results were compared with those of the quantitative PCR (qPCR) method. The positive rates of B. pertussis LAMP-LFB and qPCR were 40.7% and 38.8%, respectively, and the agreement between the LAMP-LFB and qPCR results was 98%, with a kappa value of 0.96. The whole process of LAMP-LFB can be completed within 1 h, which is much shorter than that of qPCR, including about 15 min of rapid DNA extraction, 40 min of LAMP reaction, and within 2 min of the LFB test. Collectively, the B. pertussis LAMP-LFB assay developed in this report offers a new option for the rapid, reliable, and simple diagnosis of B. pertussis infections.